Formation of microcapsules by complex coacervation. (4th December 2014) - Ach, Delphine; Briançon, Stéphanie; Broze, Guy; Puel, François; Rivoire, Alain; Galvan, Jean‐Marc; Chevalier, Yves
Abstract The process of encapsulation by complex coacervation includes several steps that have been investigated in order to reach a better control over the whole process. This has been carried out for the encapsulation of linseed oil by the classical gelatin/acacia gum pair of coacervating polymers. Fabrication of an oil‐in‐water emulsion is the first step that has been studied so as to reach a definite picture of the emulsification process under intermediate flow regime in a stirred unbaffled vessel. The classical scheme of oil droplet break‐up by turbulent eddies in the turbulent inertial regime gave a fair agreement with the experiments and can be used as a possible framework for a process scale‐up. Polynuclear microcapsules containing several oil droplets have been obtained during the deposition of the coacervate onto the surface of oil droplets. According to the emulsification conditions and microparticles growth caused by multiple droplets encapsulation, microcapsules of ∼130 µm were produced. A video probe immersed in the stirred vessel allowed an in situ monitoring of the successive events taking place as acid was added into the medium. This technique allows dynamic observations of microcapsules formation. These observations confirmed the deposition of coacervate droplets around oil drops and clearly showed that the formation of coacervate particles and their deposition onto oil droplets were successive events.